New mineralogical, geochemical and isotopic data of the Au-fulfide ores in the Suoi Cun area - Anh, Tran Tuan (Vietnam Journal of Earth Sciences, 2015)
The gold-sulphide mineralization of the Suoi Cun area are discovered along Suoi Cun downstream, locating near by the No.3 Road. They are vein and veinlet of quartz - chalcedone, cross-cuting volcanic and terrigenous sediments of the Song Hien Formation (T1Sh). Major mineral compositions are pyrite, arsenopyrite, and autogenous gold with chemical characteristics as followed:  pyrite containing high content of As, sometimes containing Au; elongated arsenopyrite needles, characterized by low As, high S, the ratio S / As> 1.1 and often contain 2.9-13.05 ppm of Au; in the composition of native gold often present Hg. The geochemical characteristics of ore including high Au, As, Hg, (Sb). Sulfur isotopes (d34S ) in pyrite ranges from -2.9 to 9.2 and those in arsenopyrite vary from -2.5 ‰ to 1.9 ‰ , demonstrated gold-sulfide mineralization type here is low-temperature hydrothermal Au-As correlation with early Triassic volcanic activity of Song Hien Formation.ReferencesA.S. Borisenko, Trần Trọng Hòa, A.E. Izokh, Ngô Thị Phượng, Trần Tuấn Anh, Bùi Ấn Niên, A.V. Travin, 2004: Stages of formation of gold mineralization in the central Việt Nam. Journal of GEOLOGY, Series B, No 28/2006, p71-82. Do Hai Dzung, 1994: Hydrothermal and epithermal gold mineralization in Vietnam and their forming tempreture. Inter. Symp. Geol. Expl. and Dev. of Energy and min. Res. Vietnam and adja. reg. Hanoi. Lê Văn Đệ, Nguyễn Thị Thục Anh, 1997: Đặc trưng các mỏ vàng nhiệt độ thấp và vấn đề khoáng hoá vàng nhiệt độ thấp ở Việt Nam. TC Địa chất, Loạt A, No.241, tr. 30-38. Fleet, M.E., Mumin, A.H., 1997: Gold-bearing pyrite and arsenopyrite from Carlin Trend gold deposits and laboratory synthesis: American Mineralogist, v. 82, p. 182–193. Genkin, A.D., Bortnikov, N.S., Cabri, L.J., Wagner, F.E., Stanley, C.J., Safonov, Y.G., McMahon, G., Friedl, J., Kerzin, A.L., and Gamyanin, G.N., 1998: A multidisciplinary study of invisible gold in arsenopyrite from four mesothermal gold deposits in Siberia, Russian Federation: ECONOMIC GEOLOGY, v. 93, p. 463-487. Trần Trọng Hòa (chủ biên), 2005: Nghiên cứu quy luật thành tạo khoáng sản quý hiếm liên quan tới hoạt động magma khu vực Miền Trung và Tây Nguyên. Báo cáo tổng kết đề tài độc lập cấp nhà nước, mã số DL-2003/07. Lưu trữ Trung tâm TT Khoa học Công nghệ Quốc Gia. Trần Trọng Hòa, Borisenko A.S. (đồng chủ biên), 2006: Nghiên cứu phát hiện các kiểu quặng hóa vàng mới (Au-Sb-Hg) trên lãnh thổ MBVN. Báo cáo tổng kết đề tài HTQT do Viện KHCNVN hỗ trợ. Lưu trữ Viện ĐC. Trần Trọng Hòa, A.S. Borisenko, Ngô Thị Phượng, A.E. Izokh, Trần Tuấn Anh, Hoàng Hữu Thành, Vũ Văn Vấn, Bùi Ấn Niên, Hoàng Việt Hằng, Trần Hồng Lam, 2006: Nghiên cứu xác lập các kiểu mỏ vàng mới (Au-Sb-Hg) liên quan tới hoạt động magma miền Bắc Việt Nam. Báo cáo tổng kết đề tài Hợp tác Quốc tế do Viện KHCNVN tài trợ (2005-2006). Lưu trữ viện Địa chất, 51tr. Trần Trọng Hòa (chủ biên), 2010: Nghiên cứu nguồn gốc, điều kiện thành tạo một số hệ magma - quặng có triển vọng về Pt, Au, Ti-V ở Việt Nam. Báo cáo tổng kết đề tài HTQT theo Nghị định thư VN-LB Nga. Lưu trữ Viện ĐC, Hà Nội, 217 tr. Trần Trọng Hòa, Nevolko P., Ngô Thị Phượng, Trần Tuấn Anh, Phạm Thị Dung, Bùi Ấn Niên, Nguyễn Xuân Huyên, Nguyễn Thùy Dương, Vũ Hoàng Ly, Trần Văn Hiếu, 2013. Các tụ khoáng vàng-sulfide trong các thành tạo lục nguyên - carbonat rift Sông Hiến, ĐBVN. Tuyển tập Báo cáo KHCN toàn quốc năm 2013. ISBN: 978-604-59-0693-4; tr. 131-140. Hoffman, E.L., 1992: Instrumental Neutron Activation in Geoanalysis. Journal of Geochemical Exploration, volume 44, pp. 297-319. Hoffman, E.L., Clark, J.R. and Yeager, J.R. 1998: Gold analysis-Fire Assaying and alternative methods. Exploration and Mining Geology, Volume 7, p.155-160. Johan, Z., Marcoux, E., and Bonnemaison, M., 1989 : Distribution de Au, Sb, As et Fe dans l’arsenopyrite aurifere du Chatelet et de Villeranges (Creuse, Massif Central francais): Les Comptes rendus de l’Académie des sciences, v. 308, p.293-300. K.R. Kovalev, Yu.A. Kalinin, E.A. Naumov, M.K. Kolesnikova, V.N. Korolyuk, 2011 : Gold-bearing arsenopyrite in eastern Kazakhstan gold-sulfide deposits. Russian Geology and Geophysics 52, 178-192. Polyakov G.V., Nguyễn Trọng Yêm, Balykin P.A., Trần Trọng Hòa, Hoàng Hữu Thành, Trần Quốc Hùng, Ngô Thị Phượng, Petrova T.E., Vũ Văn Vấn, 1996: Các thành tạo mafic-siêu mafic Permi - Trias miền Bắc Việt Nam. Nxb. KHKT, Hà Nội, 172tr. I. Saha, A.S Venkatesh, 2002: Invisible gold within sulfides from the Archean Hutti-Maski schist belt, Southern India. Journal of Asian Earth Sciences 20, p-449-457. R. Seal, 2001: Sulfur Isotope Geochemistry of Sulfi de Minerals. Reviews in Mineralogy & Geochemistry, Vol. 61, pp. 633-677. Seal, R.R., II, Ayuso, R.A., Foley, N.K., Clark, S.H.B., 2001: Sulfur and lead isotope geochemistry of hypogene mineralization at the Barite Hill gold deposit, Carolina slate belt, southeastern United. Tarnocai, C.A., Hattori, K., and Cabri, L.J., 1997: “Invisible” gold in sulfides from the Campbell mine, Red Lake greenstone belt, Ontario: Evidence for mineralization during the peak of metamorphism: Canadian Mineralogist, v. 35, p. 805-815. Trần Văn Trị (chủ biên), 2000: Tài nguyên khoáng sản Việt Nam. Cục Địa chất và Khoáng sản Việt Nam, 214tr. Trần Văn Trị, Vũ Khúc (đồng chủ biên), 2010: Địa chất và tài nguyên Việt Nam. Nxb. Khoa học Tự nhiên và Công nghệ, 589tr. Wu, X., and Delbove, F., 1989: Hydrothermal synthesis of gold-bearing arsenopyrite: Economic Geology, v. 84, p. 2029-2032.